Improving Methane Generation by Co-Digestion of Sewage Sludge and Petrochemical Wastewater: Influence of Heat and Alkali Pretreatment - Siddique, Md. Nurul Islam; Zaied, B. K.; Krishnan, S.; M. F., Ahmad (Asian Publication Corporation, 2019)
With the target of amplifying methane generation from sewage sludge (SS), co-digestion with petrochemical wastewater (PWW) was examined. In addition, the use of both 165 °C heat treatment and alkali pretreatment to mixed SS/PWW wastewater was assessed. Batch tests demonstrated that refractory materials were generated from pretreatment for petrochemical wastewater at the 165 °C heat and alkali pretreatments at the 75 or 115 °C and with pH value of 8, 9 or 10 producing enhanced preliminary methane generation percentage and a little effect for generation capacity of methane of the miscellaneous waste (+3–6 %). Anaerobic reactors which were operated more than four months semi-continuously with sewage sludge and petrochemical wastewater mix with the proportion of 85:15, 55:45 and 85:15 pretreated at alkaline environments maintaining the temperature of 75 °C and pH = 8. This pretreatment enhanced the production of methane at semi-continuous anaerobic reactors to + 59 %. Finally, this investigation demonstrated the viability of the co-digestion of sewage sludge with a higher ratio of petrochemical wastewater [45 % volume, 50 % volatile solid (VS) and 74 % COD, comparable with volatile fatty acids of 8 g L–1]. The system produced an exact methane of 363 mL CH4 g–1 VS while only sewage sludge generated 117 mL CH4 g–1 VS.